SECTIONS OF CULTURAL AND PUBLIC SOCIETIES ACTING IN POBEREZHIA VILLAGE UNTIL SEPTEMBER 1939 - Мойсишин, В. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the cultural-educational, youth and cooperative sections of Ukrainian societies operating on the territory of the Poberezhia village in Tysmenytsia district of Ivano-Frankivsk region since the end of the nineteenth century until September 1939.